Wireless Communication for Remote Power Monitoring on Utility Electric. Issue 1 (June 2019) - Azhar; Kamal, M; Subhan
Abstract: One of the results of the monitoring of electric power is to perform monitoring and security analyses. among others. a power utility electricity namely electric parameter monitor way such as voltage, current. power factor. frequency, apparent power. real power. reactive power and electric energy, Operation power remote monitoring this work based on data or electrical parameter information displayed by the power meter PM9C then forwarded to ethernet gateway, In this research the method of electrical parameter data communication that is by utilizing the device wireless ADSL2 + modem router to transmit electrical parameters and data received by the personal computer, Powerlogic EGX300 software displays two groups of electrical parameter data is real time page and device logging, On the real time page consists of a single device pages. trending and device summary, Device intended for logging access each measuring device which is connected to utility power, The results of the communication data without wires. in the monitoring of the powerlogic EGX300 software can display data parameters in the form of electricity metering. electrical parameter data and trending curve. Electrical parameter data include voltage. current. power factor. frequency. apparent power. real power. reactive power and electric energy (kWh. kVARh. kVAh).